ХҮН АМЫН АМЬДРАЛЫН ЧАНАРЫГ ДЭЭШЛҮҮЛЭХ АСУУДЛЫГ ТӨРИЙН БОДЛОГОД ТУСГАХ НЬ - М.Батбаатар (Politology, 2023)
There are lot of changes in livelihood and its surrounding environment, attitude, immediate challenges and demand of people those are living in open market system after social and economic transmission.These comprehensive changes are ongoing at individual level to family, group to community and further society to the environment. The key concept to describe the growth and social progress is quality of living. Countries in modern world tend to express their social and economic growth by the growth of quality of life of their population. Present status of social growth depends on social security, welfare, level of consumption and satisfaction of population of the country. Quality of life index becomes main indicator for the development of the country as well as main indicator to compare growth level among the countries. Thus scientifically based evaluation is in great demand to compare changes emerged in quality of living of Mongolians in market society with other indexes for quality of living among different countries as referred to relevant studies and methodologies. Government policy and actions were always delayed when it is needed and there is gap of vision and assumptions for possible events in the future as we analyze existing policies to ensure quality of living for population and relevant social and economic studies. There is great demand of policy to support and improve quality of living for population as reflecting particularity and demand of each age group of population we concluded by this study